Kinesiophobia Levels in Patients with Parkinson's Disease: A Case-Control Investigation. - Jiménez-Cebrián, Ana María; Becerro-de-Bengoa-Vallejo, Ricardo; Losa-Iglesias, Marta Elena; De Labra, Carmen; Calvo-Lobo, César; Palomo-López, Patricia; Martínez-Jiménez, Eva María; Navarro-Flores, Emmanuel María (MDPI, 2021)
Multiple sclerosis (MS) is a neurological, chronic, inflammatory, and progressive disease with musculoskeletal problems and neurodegenerative disorders that causes worsening of the health status of patients. The aim of this study was to determine the level of depression in MS patients compared to a population of healthy subjects. The established sample size was 116 subjects matched with the same age, sex, and body mass index. The subjects were recruited from different multiple sclerosis associations and neurology clinics in different public health areas (case group n = 58) and healthy subjects from the same locality (control group n = 58). The scores and categories of the Beck Depression Inventory (BDI) in its Spanish version were collected. There was a clear statistically significant difference (p < 0.05) in the BDI scores between both groups. As a result, we found that the subjects with MS presented worse results with BDI = 9.52 ± 7.70 points compared to the healthy subjects with a BDI score = 5.03 ± 5.14. Within the BDI categories, there were statistically significant differences (p < 0.001), which were greater for the MS group. Depression is a dangerous factor for MS patients, being a trigger for a poorer quality of life.
Keywords: Parkinson, Enfermedad de; Ejercicio físico - Aspectos psicológicos; Movement disorders; Parkinson's disease; Musculoskeletal and neural physiological phenomena